2012
DOI: 10.1016/j.cmet.2012.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Iron Homeostasis Regulates the Activity of the MicroRNA Pathway through Poly(C)-Binding Protein 2

Abstract: SUMMARY MicroRNAs (miRNAs) control gene expression by promoting degradation or repressing translation of target mRNAs. The components of the miRNA pathway are subject to diverse modifications that can modulate the abundance and function of miRNAs. Iron is essential for fundamental metabolic processes, and its homeostasis is tightly regulated. Here we identified iron chelators as a class of activator of the miRNA pathway that could promote the processing of miRNA precursors. We show that cytosolic iron could re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 44 publications
(68 reference statements)
1
66
0
Order By: Relevance
“…Recently, we have identified iron chelators as a class of enhancers for the miRNA/RNAi pathway in a way that these chelators could promote the processing of both miRNA precursors and short hairpin RNAs (shRNAs) [67]. We found that cytosolic iron, but not heme, regulated the activity of the miRNA pathway through poly(C)-binding protein 2 (PCBP2), but not its analogue PCBP1.…”
Section: Iron-mediated Control Of Mirna Biogenesismentioning
confidence: 89%
See 1 more Smart Citation
“…Recently, we have identified iron chelators as a class of enhancers for the miRNA/RNAi pathway in a way that these chelators could promote the processing of both miRNA precursors and short hairpin RNAs (shRNAs) [67]. We found that cytosolic iron, but not heme, regulated the activity of the miRNA pathway through poly(C)-binding protein 2 (PCBP2), but not its analogue PCBP1.…”
Section: Iron-mediated Control Of Mirna Biogenesismentioning
confidence: 89%
“…When cytosolic iron is low, PCBP2 could multimerize, bind to miRNA precursors, and present them to Dicer for more efficient miRNA processing. Excess cytosolic iron will interfere with the binding of PCBP2 to miRNA precursors as well as its association with Dicer, and lead to the reduced production of mature miRNAs [67] (Figure 1). …”
Section: Iron-mediated Control Of Mirna Biogenesismentioning
confidence: 99%
“…To make the reporter system more reliable and efficient, the stable cell clone, Clone#3 mentioned above, was infected with lenti-RFP to select the cell clones named as Clone#3/RFP with appropriate expression of RFP in order to avoid significant toxicity to cells caused by the high level of RFP. With this assay system, well-to-well GFP/RFP ratio could be employed as criterion to evaluate whether the GFP level alterations was really caused by enhanced RNAi activity instead of cell death caused by compound toxicity, and vice versa for the elevated EGFP levels [35] (Figure 2). …”
Section: Gfp Report Assay To Dissect the Rnai/mirna Pathway In Livingmentioning
confidence: 99%
“…More easily, HEK-293 cells were transfected with plasmid harboring the short hairpin against fire fly luciferase (shFFL) and single stable clones were isolated to overexpress the shFFL. The shFFL clone cells were transfected with plasmid si CHECK harboring the FL and RL driven by different promoters, and the transfected cells were treated with small molecules for luciferase assays [35]. Like the EGFP-shEGFP-RFP reporter assay system, this assay is not biased towards or against any specific components of miRNA pathway either because in the report cells, the RFL serves as internal control to distinguish the false alteration of FFL/RL caused by drug-conferred cell growth inhibition or death as well as promotion of cell growth.…”
Section: Luciferase-based Reporter Assay System To Monitor the Activimentioning
confidence: 99%
“…PCBP2 interacts with MAVS, an adaptor protein that activates innate immune responses to viral RNA (7). PCBP2 contributes to microRNA (miRNA) processing in cells by interacting with both Dicer and precursor miRNA to enhance processing into mature miRNA (8). PCBP1 and PCBP2 function in cellular iron trafficking by binding iron and delivering it directly to iron-dependent enzymes via metal-mediated protein-protein interactions (9).…”
mentioning
confidence: 99%